Validade e consequências sociais das avaliações em contextos de ensino de línguas - Scaramucci, Matilde V. R. (Linguarum Arena, 2018)
: The concept of validity is so central to testing and assessment that it would be practically impossible to research it or practice it without taking this concept into consideration. Motivated largely by the recent developments of performance assessment, which assesses language use in social contexts, however, this concept has been through extensive review in meaning and comprehensiveness to the point of becoming one of the most discussed and controversial concepts in the field of language assessment nowadays, or, as pointed out by Chapelle (1999), one of the most interesting and important aspects in Applied Linguistics. My aim in this article is to discuss the modern or expanded concept of validity/validation (as opposed to the traditional concept), which takes into consideration not only the evidencial basis but also the social consequences/washback in validating a test (Messick 1989).